Plasmon-Exciton Resonant Energy Transfer: Across Scales Hybrid Systems. (17th May 2016) - El Kabbash, Mohamed; Rahimi Rashed, Alireza; Sreekanth, Kandammathe Valiyaveedu; De Luca, Antonio; Infusino, Melissa; Strangi, Giuseppe
Abstract : The presence of an excitonic element in close proximity of a plasmonic nanostructure, under certain conditions, may lead to a nonradiative resonant energy transfer known as Exciton Plasmon Resonant Energy Transfer (EPRET) process. The exciton-plasmon coupling and dynamics have been intensely studied in the last decade; still many relevant aspects need more in-depth studies. Understanding such phenomenon is not only important from fundamental viewpoint, but also essential to unlock many promising applications. In this review we investigate the plasmon-exciton resonant energy transfer in different hybrid systems at the nano- and mesoscales, in order to gain further understanding of such processes across scales and pave the way towards active plasmonic devices.